Armed action in Algeria during the First World War And its relation to the German Ottoman propaganda - beldja, Abdul Qadir (The Algerian Historical Journal, 2026)
During the First World War, Algeria experienced protests following the severe blockade of Algerians by renewing the code of indigénat, supporting the authority of the governor general by organizing deterrent courts and deciding to impose conscription, in addition to declaring a state of emergency. On the other hand, Germany claimed to be a saviour of Islam, in addition to being an ally of the Ottoman Empire, a symbol of the Islamic Caliphate, which in turn called for sacred jihad against the enemies of the Islamic religion. In this context, this study highlights French colonial policy in Algeria during this period, and its role in the emergence of the popular protest movement, and what is the relationship of German-Ottoman propaganda to this?